HUBUNGAN ANTARA TINGKAT PENGETAHUAN IBU TENTANG PERAWATAN TALI PUSAT TERBUKA DENGAN LAMA PELEPASAN TALI PUSAT DI WILAYAH KERJA PUSKESMAS SAYUNG I KABUPATEN DEMAK - Ulvi Chamidah; Kristina Maharani; Siti Juwariyah (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
The mortality causes of babies in Demak regency, in 2020, were low weight birth (43.87%), Asphyxia (16.9%), Tetanus Neonatorum (1%), and Sepsis (5.3%), and inherited abnormality (30.6%). The umbilical cord is a unique tissue and could be the infection source for newly born babies. Umbilical care becomes a behavioral realization that must be improved with excellent knowledge of taking care of the cord. This excellent behavior to take care of the cord could improve the behavior of taking care of the umbilical cord. Thus, the cord will be easily detached. Lack of adequate knowledge about umbilical cord will lead to incorrect administration of using traditional medicine which highly leads to neonates infection. This research determined the correlation between the mother's knowledge about the opened umbilical cord care and the detachment period of the umbilical cord. This analytic correlation research used a cross-sectional design. The sample consisted of all mothers, 64 mothers, with an estimated period of birth from June to July 2022 in the working area of Sayung 1 Health Care, Demak Regency. The researchers analyzed the data with univariate and bivariate analyses. The results showed the correlation between the mother's knowledge and the opened umbilical cord during the detachment period. The obtained p-value was 0.000, lower than 0.05. Keywords: Mother knowledge, Opened umbilical cord care, Umbilical cord detachment